2017
DOI: 10.5604/01.3001.0010.2717
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic HCV Infection with the New Direct Acting Antivirals (DAA): First Report of a Real World Experience in Southern Brazil

Abstract: Real world experience with DAA therapy in Southern Brazil showed a high rate of SVR and excellent tolerability. Failure to achieve SVR was mainly observed among patients with at least one negative predictor of response: cirrhosis and/or genotypes 1a or 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…In a highly representative population of patients infected with HCV throughout the country and treated with the same therapeutic regimen, the overall SVR rates were higher than 95% [ 20 ]. In a real-world cohort from three hepatology centers from southern Brazil, SVR was achieved in 95% of patients treated with second-generation DAAs [ 21 ]. In Spain, rates of 96.8% and 95.8% were found in two cohorts of individuals infected with HCV with genotype 1 treated by second-generation DAAs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a highly representative population of patients infected with HCV throughout the country and treated with the same therapeutic regimen, the overall SVR rates were higher than 95% [ 20 ]. In a real-world cohort from three hepatology centers from southern Brazil, SVR was achieved in 95% of patients treated with second-generation DAAs [ 21 ]. In Spain, rates of 96.8% and 95.8% were found in two cohorts of individuals infected with HCV with genotype 1 treated by second-generation DAAs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, screening and full-text assessment resulted in 20 included studies (14 manuscripts and 6 conference abstracts) that reported on SVR12 by DAAs in 7,393 individuals from South American countries ( Figure 1). [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] A total of 16 studies were published in English, two in Spanish 40,44 and two in Portuguese. 29,33 In addition, included studies were performed in Sofosbuvir/Simeprevir ± Ribavirin (SOF/SIM ± RBV), Sofosbuvir/ Ledipasvir (SOF/LDV) or Ombitasvir/Paritaprevir/Ritonavir + Dasa buvir ± Ribavirin (OBV/PTV/r/DSV ± RBV).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…In Brazil, DAAs were incorporated by the Ministry of Health for the treatment of hepatitis C under the Unified Health System (SUS) since 2015 (Ministério da Saúde, 2018). Unfortunately, there is little data about the efficacy of DAAs in Brazil, with some information found in the study by Sette Jr et al (2017).…”
Section: Introductionmentioning
confidence: 99%